Peningkatan Pengetahuan Kader Posyandu Pada Hipertensi Dengan Edukasi Berbasis Aplikasi Di Desa Godog Dan Tanjung Sari Kabupaten Garut - Eva Daniati; Tantri Puspita; Muhammad Hadi Sulhan; Sri Yekti Widadi; Andhika Lungguh Perceka; Wahyudin (INTEGRATIF: Jurnal Pengabdian Kepada Masyarakat, 2026)
Hypertension is a global health problem with high prevalence and is a major risk factor for cardiovascular diseases. Posyandu cadres have a strategic role in early detection and health promotion in the community, yet their knowledge about hypertension is often limited. This community service activity aims to increase the knowledge of Posyandu cadres about hypertension through health education in Godog and Tanjung Sari Villages in Karangpawitan District, Garut Regency. The methods used were interactive lectures and group discussions which involved 33 Posyandu cadres. Evaluation was conducted using pre-test and post-test with a 15-question instrument. The results showed an increase in the average knowledge score from 12.55 to 13.21, with an increase in the percentage of cadres with good knowledge category from 75.8% to 87.9%. Health education demonstrated a tendency to improve the knowledge of Posyandu cadres, as indicated by the comparison of pre-test and post-test scores.